Penguatan Standar Pengelolaan Homestay Desa Wisata melalui Pendampingan Partisipatif Berbasis Inovasi Layanan Kreatif - Muhammad Fauzan Noor; Dini Zulfiani (PT Cendekia Education Center, 2026)
This community service program aims to strengthen homestay management standards in Sangkuliman Tourism Village thru participatory assistance based on innovative creative services. The focus of the activities is directed toward improving the competencies of homestay managers in aspects of service standards, hospitality, creative housekeeping skills, and the preparation of village homestay profiles. The implementation method used an interactive training and mentoring approach over two days, involving around 10 participants from homestay owners, Pokdarwis, Karang Taruna, and the community. The activities included lectures, hospitality simulations, napkin folding and towel art practices, as well as assistance in compiling homestay profiles with pre-test and post-test evaluation instruments. The results showed an increase in understanding of homestay standards from 55% to 85%, hospitality from 60% to 88%, towel art skills from 20% to 90%, and the ability to compile homestay profiles from 30% to 85%. The program outputs also included the documentation of 10 homestay units, the compilation of one village homestay profile document, achieving ≥80% participant competence, and the initial formation of a service SOP draft. Overall, this program effectively enhances the readiness of homestay services and strengthens the initial capacity of village tourism managers, although the sustainability of the impact requires further assistance and regular monitoring.